2022
DOI: 10.1097/wco.0000000000001074
|View full text |Cite
|
Sign up to set email alerts
|

The recent surge of functional movement disorders: social distress or greater awareness?

Abstract: Purpose of reviewTo analyze the interrelated factors that have led to the striking increase in functional movement disorders in recent years, with a focus on functional tic-like behaviours (FTLB).Recent findingsThe sudden onset of FTLB has been widely observed in several countries since the beginning of the SARS-CoV-2 pandemic, whereas it was previously very rarely reported. Pandemic-related FTLB typically occur in young females, share complex, disabling and tic-lookalike patterns, and are usually triggered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 52 publications
3
24
0
1
Order By: Relevance
“…Traditionally considered uncommon amongst functional neurological symptoms [1], FTLBs have attracted a dramatic rise in attention among movement disorder specialists, neuropsychiatrists, paediatricians, and the public at large during the pandemic. There has been a sharp increase in the numbers of adolescents and young adults presenting to paediatric health services and, in a subgroup, an increased exposure to videos of FTLBs on popular social media platforms between 2019 and 2022 has been documented [4][5][6][7][8][9][10][11][12]. Some of these patients became so rapidly functionally impaired that they sought urgent help from emergency departments or fast-track referrals to specialist clinics [4,10,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally considered uncommon amongst functional neurological symptoms [1], FTLBs have attracted a dramatic rise in attention among movement disorder specialists, neuropsychiatrists, paediatricians, and the public at large during the pandemic. There has been a sharp increase in the numbers of adolescents and young adults presenting to paediatric health services and, in a subgroup, an increased exposure to videos of FTLBs on popular social media platforms between 2019 and 2022 has been documented [4][5][6][7][8][9][10][11][12]. Some of these patients became so rapidly functionally impaired that they sought urgent help from emergency departments or fast-track referrals to specialist clinics [4,10,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…63 Indeed, several studies have proposed that the functional tics seen in association with social media use are likely caused by a combination of complex factors, including predisposing factors such as pre-existing genetic risk factors for depression and anxiety, poor adaptive or coping behaviors, family and peerrelated stressors, pandemic-specific impacts on mental health, social isolation, and behavioral modeling through exposure to social media. 16,30,62 Regardless, several case reports, case series, and cohort studies have collectively identified over 100 patients that have been newly presented to a variety of institutions with what is believed to be FTLB (Table 1). Although the causative effect of social media has not been definitively linked to the onset of FTLBs, it is hard to ignore the similarities in pattern and behavior between the social media influencers and the patients presenting to movement disorder clinics around the world.…”
Section: Ticsmentioning
confidence: 99%
“…This global phenomenon has resulted in concern that in the context of isolation and stress, attention and exposure to inaccurate portrayals of tics on social media may be fueling this notable rise. 16,17 There are also concerns that these social media platforms may unintentionally increase misperceptions of TS, furthering stigma and the sequelae of living with a stigmatized disorder. 16,18 Therefore, it is important not only to educate the general public about TS but also to educate individuals presenting with functional tics thought to be largely influenced by social media in order to reduce stigma, improve quality of life for those who have TS, and improve outcomes for individuals with functional tics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2019 and 2022, there has been a sharp rise in the number of adolescents/young adults seeking urgent help for complex abnormal movements and vocalizations that resemble symptoms of primary tic disorders, which in many cases involved attendance to emergency departments or fast-track referrals to specialist clinics [ 1 , 2 , 3 ••]. In an effort to describe this new clinical presentation, an international group of clinicians and specialists agreed the term functional tic-like behaviors (FTLB) reflected that the behaviors tics and shared common features with other functional movement disorders (FMD) [ 3 ••].…”
Section: Introductionmentioning
confidence: 99%